Performance Analysis of DCSK-BDR Systems over Nakagami-m Fading Channels. Issue 2 (3rd March 2020) - Kumar, Atul; Sahu, P. R.
Abstract : In this paper, a differential chaos shift keying bidirectional relaying (DCSK-BDR) scheme is proposed in which two source nodes exchange their information through a relay node. By using network coding at the relay, the proposed scheme offers spectrum and energy efficiency over the conventional DCSK transmission scheme for end-to-end communication. Analytical expressions for the probability density function (PDF) of the signal-to-noise ratio (SNR) of each hop are derived for Nakagami- m fading channel. The end-to-end average bit error rate (BER) of the system is evaluated. Throughput of the proposed schemes is also presented and compared. Numerical results are verified with the simulation results and plotted for different parameters.